Multi‐lead cephalic venous access and long‐term performance of high‐voltage leads. (18th February 2021) - Akhtar, Zaki; Harding, Idris; Elbatran, Ahmed I.; Gonna, Hanney; Mannakkara, Nilanka N.; Leung, Lisa W. M.; Zuberi, Zia; Bajpai, Abhay; Pearse, Simon; Cox, Andrew T.; Li, Anthony; Jouhra, Fadi; et al.
Abstract: Background: Cardiac resynchronization therapy‐defibrillator (CRT‐D) implantation via the cephalic vein is feasible and safe. Recent evidence has suggested a higher implantable cardioverter‐defibrillator (ICD) lead failure in multi‐lead defibrillator therapy via the cephalic route. We evaluated the relationship between CRT‐D implantation via the cephalic and ICD lead failure. Methods: Data was collected from three CRT‐D implanting centers between October 2008 and September 2017. In total 633 patients were included. Patient and lead characteristics with ICD lead failure were recorded. Comparison of "cephalic" (ICD lead via cephalic) versus "non‐cephalic" (ICD lead via non‐cephalic route) cohorts was performed. Kaplan–Meier survival and a Cox‐regression analysis were applied to assess variables associated with lead failure. Results: The cephalic and non‐cephalic cohorts were equally male (81.9% vs. 78%; p  = .26), similar in age (69.7 ± 11.5 vs. 68.7 ± 11.9; p  = .33) and body mass index (BMI) (27.7 ± 5.1 vs. 27.1 ± 5.7; p  = .33). Most ICD leads were implanted via the cephalic vein (73.5%) and patients had a mean of 2.9 ± 0.28 leads implanted via this route. The rate of ICD lead failure was low and statistically similar between both groups (0.36%/year vs. 0.13%/year; p  = .12). Female gender was more common in the lead failure cohort than non‐failure (55.6% vs. 17.9%, respectively; p  = .004) as was hypertension (88.9% vs. 54.2%, respectively, p  = .038). On multivariate Cox‐regression, female sex ( p  = .008; HR, 7.12 [1.7−30.2]), and BMI ( p  = .047; HR, 1.12 [1.001−1.24]) were significantly associated with ICD lead failure. Conclusion: CRT‐D implantation via the cephalic route is not significantly associated with premature ICD lead failure. Female gender and BMI are predictors of lead failure.